2013
DOI: 10.1080/09537287.2013.798084
|View full text |Cite
|
Sign up to set email alerts
|

A knowledge chain management framework to support integrated decisions in global supply chains

Abstract: Knowledge management has been identified as a key enabler to achieve organisation's value chain competitiveness. It, however, has been facing fresh challenges in a global supply chain setting. This paper proposes a global knowledge chain management (GKCM) framework that identifies and prioritises critical knowledge that a global supply chain can focus on to support integrated decisions. The framework explores three types of global context knowledge, namely global market knowledge, global capacity knowledge and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 25 publications
1
21
0
1
Order By: Relevance
“…Second, it facilitates the generation of commitment (Nelson, 2011). Third, culture enhances the stability of the organization (Liu, Moizer, Megicks, Kasturiratne, & Jayawickrama, 2014). Fourth, culture serves as a sense-making device that can guide and shape behavior (Wang & Rafiq, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Second, it facilitates the generation of commitment (Nelson, 2011). Third, culture enhances the stability of the organization (Liu, Moizer, Megicks, Kasturiratne, & Jayawickrama, 2014). Fourth, culture serves as a sense-making device that can guide and shape behavior (Wang & Rafiq, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…KCT has been empirically examined at both organizational and interorganizational levels (Ponis & Koronis, ; Tseng, ). Based on KCT, Liu, Moizer, Megicks, Kasturiratne, and Jayawickrama () develop a global knowledge chain management framework that identifies and prioritizes critical knowledge that a global supply chain can focus on to support integrated decisions.…”
Section: Introductionmentioning
confidence: 99%
“…Organisations focusing on KM have identified that knowledge sharing within green SCs has been marked by increased productivity and sustained competitive advantage (Baresel-Bofinger et al 2011;Chong et al 2013;Liu et al 2014). KM facilitates managers in obtaining, categorising and corresponding both tacit and explicit knowledge.…”
Section: Knowledge Management and Grsccmentioning
confidence: 99%